Metrics for environmental compensation: A comparative analysis of Swedish municipalities - Söderqvist, Tore; Cole, Scott; Franzén, Frida; Hasselström, Linus; Beery, Thomas H.; Bengtsson, Fredrik; Björn, Helena; Kjeller, Elsie; Lindblom, Erik; Mellin, Anna; Wiberg, Johanna; Jönsson, K. Ingemar (Journal of environmental management, 2021)
Environmental compensation (EC) aims at addressing environmental losses due to development projects and involves a need to compare development losses with compensation gains using relevant metrics. A conceptual procedure for computing no net loss is formulated and used as a point of departure for a comparative analysis of metrics used by five Swedish municipalities as a part of their EC implementation in the spatial planning context of detailed development plans. While Swedish law does not require EC in this context, these municipalities have still decided to introduce EC requirements for development projects that occur on municipality-owned land and to promote voluntary EC among private actors in development projects on private land. There is substantial variation across the municipalities studied with respect to both metrics and attributes subject to measurement, but there are also similarities: The attributes considered when assessing the need for EC in conjunction with development are not only about nature per se, but also about recreational opportunities and other types ecosystem services; semi-quantitative metrics such as scores are common while quantitative or monetary metrics are rare; and metrics are rarely applied to assess compensatory gains, focusing instead on losses from development. Streamlining across municipalities might be warranted for increasing predictability and transparency for developers and citizens, but it also introduces considerable challenges such as a need for developing consistent guidelines for semi-quantitative metrics, and to handle substitutability issues if metrics are not only applied on individual attributes but also on groups of attributes. The broad scope of attributes used by the municipalities is in line with an international tendency to broaden EC to include not only biodiversity aspects but also ecosystem services. Moreover, the EC systems applied by the municipalities are of particular importance for highlighting the crucial role of environmental management for maintaining and enhancing biodiversity and ecosystem services not only in areas having formal protection status but also in the everyday landscape. The municipalities’ experience and strengths and weaknesses associated with their EC systems are therefore relevant also in an international perspective. •Some Swedish municipalities have developed systems for environmental compensation.•A conceptual structure was applied for comparing metrics for losses and gains.•Metrics involved biodiversity aspects as well as ecosystem services.•Full equivalency analysis and benchmarking were not applied by all municipalities.•Municipal compensation systems are vital in everyday landscape management.